The next supper : the end of restaurants as we knew them, and what comes after - Mintz, Corey, 1975- (PublicAffairs, 2021)
"In 2019, the restaurant business was booming. Americans spent more than half of their annual food budgets dining out. In a generation, chefs had gone from behind-the-scenes laborers to TV stars. The arrival of Seamless, DoorDash, and other meal delivery apps was overtaking home cooking. Beneath all that growth lurked serious problems. Many of the best restaurants in the world employed unpaid cooks. Meal delivery apps were putting many restaurants out of business. And all that dining out meant dramatically less healthy diets. The industry may have been booming, but it also desperately needed to change. And, then, along came COVID-19. From the farm to the curbside pickup parking spot, everything about the restaurant business is changing, for better or worse. The Next Supper tells this story, and offers clear and essential advice for what and how to eat to ensure the well-being of cooks and waitstaff, not to mention our bodies and the environment. The Next Supper reminds us that breaking bread is an essential human activity, and charts a path to preserving the joy of food in a turbulent era"--